Impact of Coal Export Decline on East Kalimantan's Mining and Coal Industry - Randa, Abigail Brenda Pasorong; Rohmat, Erwin Agung Nur; Oktaviana, Lisda; Albab, Muhammad Hafiz; Kartiasih, Fitri (Journal of Developing Economies, 2025)
Two of Indonesia’s top export commodities are coal and lignite. However, there is a decrease in the value of coal exports in 2023. The province in Indonesia with the biggest coal reserves is East Kalimantan. This study aims to examine the condition of the mining and coal industry and its relationship with other industries, determine the leading sectors, and assess the impact of the decline in coal exports on the economy of East Kalimantan. The input-output and gross regional domestic product tables for East Kalimantan in 2016 and 2023 are used in the analysis. This study found that even though it is not a leading industry, the mining and coal sector is still an important sector for the economy of East Kalimantan. All economic sectors experienced a decline in output due to the decline in the value of coal exports (mining products) in East Kalimantan, and this sector alone felt the greatest impact—around 73.67% of the total impact in all economic sectors. To process and purify coal produced during mining, the government must establish close communication with business owners in the coal mining industry. Apart from that, the development of the downstream coal industry must also be completed immediately.